Analysis of experiences with exclusive breastfeeding among HIV-positive mothers in Lusaka, Zambia - Alice Ngoma-Hazemba; Busisiwe Purity Ncama (Taylor & Francis Group, 2016)
Background: Exclusive breastfeeding in the first 6 months offers protection from postnatal HIV infection but remains low in resource-poor settings. Documentation of experiences with exclusive breastfeeding is needed to strengthen infant feeding counselling by health care workers. Objective: To explore HIV-positive mothers' experiences with exclusive breastfeeding during the first 6 months of the infant's life. Design: A health facility- and community-based exploratory qualitative study was conducted among 30 HIV-positive mothers practising exclusive breastfeeding and meeting the selection criteria. In-depth interviews were conducted four times with the same participants at 6 days, 6 weeks, 12 weeks and 18 weeks after giving birth. Interviews were transcribed verbatim and files were imported into QRS NVivo Version 10 for coding, and data were analysed using the framework analysis. Results: We found that mothers were aware of the risks of mother-to-child transmission of HIV through breastmilk and recognised the benefits of exclusive breastfeeding to their exposed babies. However, they were particularly concerned about achieving HIV-free survival for their exposed infants because of problems faced during the first 6 months of infant feeding. Although they reported being supported by their families and/or friends, their poor health and nutrition impacted how well they cared for their infants' well-being. Conclusions: We conclude that exclusive breastfeeding was difficult to achieve because of individual circumstances. Therefore, prevention of mother-to-child transmission interventions that adopt a once-off infant feeding counselling do not achieve adequate preparation on the part of mothers to practice exclusive breastfeeding. There is a need to provide frontline health care workers with steps for consideration during infant feeding counselling.